PENYEDIAAN PELAYANAN PUBLIK DALAM PERSOALAN SAMPAH DI KOTA PEKANBARU TAHUN 2014-2016 - Hidayatullah Lubis; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In an effort to provide public services to meet the basic needs of citizens, the policy in regional management has become the responsibility of the local government itself. It is contained in Act No. 23 of 2014 on Regional Government. Environmental issues become one of the basic aspects in an effort to create an atmosphere and order in a region, it is necessary to have cooperation with third parties, namely the interregional cooperation between the borders for the implementation of Government Affairs: a. Who has cross-regional externalities; And b. Provision of more efficient public services if jointly managed. Like urban spatial plan Pekanbaru in Pekanbaru city regulation No. 8 of 2014 About waste management. This research is intended to know the waste management in Pekanbaru City in 2014-2015. Pekanbaru has 16 Temporary Disposal Sites (TPS) scattered in a compact area of Pekanbaru consisting of 12 districts currently capable of generating 500 tons of waste / day, of about 1.3 million residents. On average, 2.6 kilograms of rubbish once every resident every day. Garbage collection of garbage is always routinely done by related parties but in running its service there is still lack and dissatisfaction of society. Pekanbaru in 2013 entered in the cleanest big city in Indonesia through Adipura award, but in fact garbage management becomes problem always updated by Local Government of Pekanbaru City, problems arise due to security and coordination from various parties in providing public service garbage problem, one of The peak is the piling up of garbage in some sub-districts and there are also strike action of officers who are not respected by third parties PT. Multi Inti Guna (PT.MIG) which does not affect the management of the areas that are not harmonious in the process of waste management budget disbursement. Key Word : Waste Management, Pekanbaru Municipal Government, Roles, Office of Sanitation and Gardening.